SOCIAL AND ECONOMIC ESSENCE OF INCREASING THE WELL-BEING OF THE POPULATION BASED ON ENSURING THE ACTIVITY OF HOUSEHOLDS - Оchilоva Nargiza , Akramоvna (THE INNOVATION ECONOMY, 2025)
The socio-economic nature of the household sector, the history of its inclusion in science, and its types are studied in the article. Also, the main household incomes and their sources, which are one of today's were studied urgent problems, and analyzed and were developed proposals and recommendations